2020
DOI: 10.3390/brainsci10030172
|View full text |Cite
|
Sign up to set email alerts
|

Design Fluency in Children with ADHD and Comorbid Disorders

Abstract: Background: Attention deficit/hyperactivity disorder (ADHD) is often associated with frontal executive impairment in children. Oppositional defiant disorder (ODD) and anxiety disorders (AD) frequently accompany ADHD, but the impact of these comorbid disorders on cognition remains elusive. The five-point test (FPT), a design fluency task, has been shown to be sensitive to neurological damage, specifically to frontal lobe lesions in patients with brain injuries. The purpose of this study was to compare the perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 94 publications
(106 reference statements)
1
3
0
2
Order By: Relevance
“…The correlational analyses revealed a positive correlation between age and all FPT variables, except for repetitions and its ratio measure, and no relation with sex, confirming earlier studies showing an effect of age but no sex difference in design fluency performances [ 22 ]. The relationship between age and design fluency is consistent with studies on cognitive development in children and the FPT’s usefulness in characterizing this development [ 21 , 22 , 35 , 39 ]. Compared with inhibition (see [ 35 , 81 , 82 ] and cognitive flexibility [ 83 ], fluency would develop late as it actively involves strategizing, monitoring, and self-assessment.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…The correlational analyses revealed a positive correlation between age and all FPT variables, except for repetitions and its ratio measure, and no relation with sex, confirming earlier studies showing an effect of age but no sex difference in design fluency performances [ 22 ]. The relationship between age and design fluency is consistent with studies on cognitive development in children and the FPT’s usefulness in characterizing this development [ 21 , 22 , 35 , 39 ]. Compared with inhibition (see [ 35 , 81 , 82 ] and cognitive flexibility [ 83 ], fluency would develop late as it actively involves strategizing, monitoring, and self-assessment.…”
Section: Discussionsupporting
confidence: 84%
“…Since comorbid disorders in TS represent a major confounding factor in neuropsychological studies [ 9 ], and given that the neurological anomalies observed in TS correlate with tic severity [ 50 ], we may expect such factors to be associated with cognitive impairments beyond the mere presence of a tic disorder. Furthermore, given the paucity of studies on design fluency in TS, the detailed analysis of the present study will contribute to the literature on the subject, add to existing research on the DF profiles in clinical pediatric populations (see [ 21 , 31 , 46 , 51 , 52 , 53 ]), and thus might provide evidence to guide clinicians through assessment.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…В большей степени это относится к комбинированному типу СДВГ [2]. И хотя часть симптомов СДВГ, особенно гиперактивность, по мере взросления компенсируется, нарушение социальной адаптации и качество жизни пациентов ухудшается за счет присоединения сопутствующих депрессивных, тревожных, фобических и тикозных расстройств [3]. Симптомы сопутствующих психопатологических нарушений приобретают основное значение при ослаблении симптомов СДВГ и требуют медикаментозной коррекции и психотерапевтического вмешательства.…”
Section: Introductionunclassified